Pelaksanaan Tata Usaha Dalam Memberikan Pelayanan Akademik di SMP Negeri 24 Palembang - Choirun Niswah; Ibrahim Ibrahim; Nur Zakia (Student Scientific Creativity Journal, 2023)
This research is entitled "Administrative Implementation in Providing Academic Services at SMP Negeri 24 Palembang". This study aims to determine the implementation of administration in providing academic services and the supporting and inhibiting factors of administrative implementation in providing academic services at SMP Negeri 24 Palembang. The type of research used in this research is qualitative research. Data collected through observation, interviews, and documentation. This type of research approach is descriptive qualitative. The techniques used in data analysis are data reduction, data presentation, and drawing conclusions. To test the validity of the research data using technical triangulation and source triangulation. The results of this study indicate that the implementation of administration in providing academic services at SMP Negeri 24 Palembang has three areas, namely: 1) Implementation of student administration activities carried out by administration in archiving student data documents are still not neatly arranged due to insufficient storage space and administrative space small businesses that are only partitioned off to the teacher's room which causes the implementation of student administration to not be optimal. 2) The administrative implementation of the curriculum activities carried out by the administration is running quite well, starting from administering the completeness of the curriculum, inputting the list of student grades, dividing teacher assignments, as well as fostering the preparation of lesson plans and syllabi. 3) The administrative implementation of academic personnel has been going well starting from the preparation of school personnel for the management of academic services, sending employees to take part in training for human resource development and coordinating to maintain harmony, balance and determination in carrying out employee duties. The supporting factors are personnel and methods. The inhibiting factors are the lack of other supporting facilities and infrastructure such as document storage cabinets, administrative rooms which are only separated from the teacher's room and from sources of funds that are less profitable in supporting academic service activities.